Gestão estratégica e as competências gerenciais na estrutura financeira da organização. Um estudo de caso em uma empresa administradora de consórcios - Gündel, Adriane (2008)
This work presents a case study, in a company that offers services in the field of partnerships, located in the city of Santa Maria, RS, which uses the Strategic Planning in its activities. The research seeks to identify the competences of management of the Financial Administrative Manager in the financial structure of the company. To reach this objective, the following specific objectives were established: (1) to study the main models of strategic management proposed by the authors, currently; (2) to study the current models of structures in the financial field; (3) to identify the Strategic Planning and the Organizational and Financial Structure in the company; (4) to identify the Functions and Competences, the present ones and the expected ones, of the company s Financial Administrative Manager. To collect these data, a semi-structured interview was used, with the aid of semi-opened questionnaires and participant observation, applied to the Financial Administrative Manager, his boss and his subordinated. With these interviews it was possible to identify the way the financial structure of the company is organized, as well as to analyze the competences of management that this professional has and should have to perform his functions efficiently and to provide an optimized Strategic Management for the company.